TYPES OF POLYGLANDULAR AUTOIMMUNE SYNDROMES AT ADULTS PATIENTS WITH DIABETES MELLITUS AND THYROID DISEASES - Adriana, Gherbon (European Scientific Journal, ESJ, 2014)
Background/Objectives: Polyglandular autoimmune syndrome (PAS) is made up of a group of autoimmune disorders of the endocrine glands. The purpose of this study is to determine the types of PAS in a group of adults with thyroid diseases and diabetes mellitus (DM). Material and methods: The studied group was of 350 cases with an age between 17-79 years. The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters. Results: The prevalence of PAS in the study group was 17.14%, from which PAS I 0%, PAS II 3.14% (11.66% in the case of DM type 1 and 1.38% in the case of DM type 2, p < 0.001, X2 = 17.28) and PAS III 14% (71.66% in the case of DM type 1 vs. 2.06% in the case of DM type 2, p <0.001, X2 =200.01). The type of PAS III was type III A for type 1 diabetes and type III C for type 2 diabetes. All the patients with PAS were middle-aged women. Conclusions: In our study group we find PAS at middle-aged women, the type II and III, which are prevailed in the group with type 1 diabetes, due to autoimmune origin.